Glacial Terminations II and I as recorded in NE Iceland - Van Vliet-Lanoë, Brigitte; Guðmundsson, Agust; Guillou, Hervé; Guégan, Soléne; van Loon, A.J. (Tom); De Vleeschouwer, François (Geologos, 2011)
Volcanism in eastern Iceland has controlled the changes in glacier- and river-drainage patterns and the sedimentary budget, particularly during the Middle and Late Pleistocene. The glacial extent in NE Iceland appears to be related to the impact of volcanic activity, not only on the ice-stream dynamics, but also on the sedimentary successions. Analysis of the Jökuldalur and Jökulsa á Brù records results in a new interpretation of the changes in ice extent and ﬂow direction for at least the last two glaciations. From MIS 8 onward, the development of the Snæfell volcano apparently forced the ice stream that derived from the Vatnajökull ice cap to take another course; it also affected the offshore sedimentary budgets at the new outlet at Vopnafjördur. The MIS 6 ice sheet was thick and extensive, and associated with an ice- stream diversion to the North. The thick sedimentary complex of palaeolake Halslón was formed close to an outlet of the Vatnajökull, the Brùarjökull, during Termination II and a part of the MIS 5e interglacial. The deposits formed during MIS 5e record two climate optima interrupted by two successive glacial advances correla-ted with the mid-Eemian cooling. The deposits of the Weichselian deglaciation (Termination I) are much more limited in thickness. During the Last Glacial Maximum and the Late Glacial, glaciers also seem to have been restricted in the Jökulsa á Brù area. Valley glaciers issued from the Brùarjökull re-advanced several times in the Jökuldalur only during at least the Older Dryas, the Younger Dryas and the Preboreal. NE Iceland has undergone considerable deglaciation since the Bølling. In contrast to the conclusions of previous studies, the results presented here are consistent with data on the glaciations in other Nordic regions and can increase the understanding of the mid-Eemian cooling.